EVALUATION OF OUTCOMES OF HEMORRHOIDECTOMY USING THE LONGO PROCEDURE AT HA TINH GENERAL HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Introduction: To evaluate early outcomes of hemorrhoidectomy using the Longo technique at Ha Tinh Provincial General Hospital in 2025.Patients and Methods: A prospective descriptive study was conducted on 33 patients with grade II–III internal hemorrhoids who underwent the Longo procedure from January to December 2025. Clinical, intraoperative, and postoperative data were collected and analyzed.Results: The male-to-female ratio was 1.4:1, with a mean age of 46.5 years. Disease duration of less than 6 months accounted for 63.6%, and the main symptom was prolapsed hemorrhoids (66.7%). Patients with 3–5 hemorrhoidal piles accounted for 84.8%, with grade III hemorrhoids being most common (72.7%). The mean operative time was 28.5 minutes. The mean duration of postoperative pain was 2.7 days, with a mean VAS score of 3.6. Postoperative bleeding occurred in 1 case (3.0%). The mean hospital stay was 3.5 days. Good outcomes at discharge were achieved in 87.9% of patients. At 6-month follow-up, 6.1% had persistent symptoms, 3.0% developed anal stenosis, and 6.1% experienced mild fecal incontinence, all of which resolved completely.Conclusion: The Longo procedure for grade II and III internal hemorrhoids is a safe and effective technique, associated with less postoperative pain, rapid recovery, and a low complication rate.
Keywords: Longo procedure; internal hemorrhoids; grade II–III hemorrhoids.